2001
DOI: 10.1053/jpro.2001.23777
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of the fracture resistance and failure mode of fiber, ceramic, and conventional post systems at various stages of restoration

Abstract: Purpose: This in vitro study evaluated 6 post systems over 4 simulated clinical stages of tooth restoration to (1) determine quantitatively the fracture resistance strength at each stage when a static loading force is applied to cause failure; (2) determine the failure mode for each post system at each simulated clinical stage; and (3) determine the feasibility of removing failed post systems.Materials and Methods: Ten post systems made with various materials and designs were tested at the following 4 stages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 5 publications
4
70
0
9
Order By: Relevance
“…Several authors reported that high fracture resistance was obtained when the elastic moduli of the post and dentine were compatible with each other (Ferrari et al. 2000, Cormier et al. 2001, Akkayan & Gulmez 2002, Maccari et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported that high fracture resistance was obtained when the elastic moduli of the post and dentine were compatible with each other (Ferrari et al. 2000, Cormier et al. 2001, Akkayan & Gulmez 2002, Maccari et al.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated the favourable physical properties of fibre‐reinforced composite (FRC) posts (Asmussen et al. 1999, Cormier et al. 2001, Mannocci et al.…”
Section: Introductionmentioning
confidence: 99%
“…The use of fiber posts reduces the risk of root fracture significantly as the modulus of elasticity of these posts is close to that of dentin (147). Research has demonstrated that a significant proportion of metal post failures are due to terminal root fractures (149,150). Research has demonstrated that a significant proportion of metal post failures are due to terminal root fractures (149,150).…”
Section: Fiber Postsmentioning
confidence: 99%